Friction and wear characteristics of robust carbon-carbon composites developed solely from petroleum pitch without reimpregnation - Shishobhan Sharma; Bharat Patel; Rasmika Patel (Friction)
Abstract Friction and wear characteristics correlating the fiber reinforcement percentage of carbon-carbon (C/C) composites solely developed from petroleum pitch matrices were investigated. This study exhibits the tribo-characteristics of C/C composites developed in a single-step carbonization process for varying loads for the first time without a reimpregnation process. A pin-on-disc tribometer with a sliding speed of 0.5 m/s and loads of 5, 10, and 20 N with a flat tool grade stainless steel pin as a static partner was employed. Further, polarized light optical and scanning electron microscopes (SEM) were utilized for a morphological analysis. Elastic modulus and strength were determined by a compression test. A result analysis is conducted to analyze sliding wear accompanied with minor abrasion. The composites with a high percentage of reinforcement exhibit credible wear resistance and mechanical robustness.